Kesalahan Siswa dalam Memahami Konsep Kinematika Gerak Lurus - Anisa Magfira; Kamaluddin; Darsikin (Universitas Tadulako, 2021)
This research is a qualitative descriptive study whose data is about understanding the concept of straight motion kinematics material using CRI (Certainty of Response Index). This study aims to describe, identify and analyze students' understanding of the kinematics concept of straight motion. The samples taken were 20 students of grade 11 IPA I SMA Negeri 1 Palu. The instrument used is multiple choice questions as many as 14 questions that have been selected through a validation test. Students answer the question by adding CRI points (0-5) according to the student's level of confidence with reasons. Students can be declared to understand the concept, do not understand the concept or experience misconceptions by comparing whether or not the answers to the questions given are correct with the CRI scores filled in by students. The results obtained in this study, namely for students who understand the concept have a percentage of 13.57%, while misconceptions are 38.57% and those who do not understand the concept are 47.86%. This shows that students tend not to understand the concept because students are only able to memorize without understanding the material taught by the teacher so that students tend to forget. Some of the misconceptions (wrong concepts) that occur in students are identified, among others; analyzing images, distances, displacements on story problems and graphs on glb, glbb and parabolic motion.